Analisis Jenis Tuturan,Implikatur Dan Kesantunan Dalam Wacana Tutur Vicky Prasetyo Kajian Pragmatik - Ardiyanti, Riza, Prof. Dr. Abdul Ngalim, MM.,M.Hum, Dr. Muhammad Rohmadi, M.Hum (2015)
This research aim to: description and explaining saying type used in Vicky Prasetyo discourse say, description and explaining implicature type used in Vicky Prasetyo discourse say, description and explaining principal deviation of suavity was used in Vicky Prasetyo discourse say. This research type was descriptive qualitative study. The data sorce in this research was TTD pronounciation said by Vicky Prasetyo able to download from youtube media upon which study. The data collecting technique in this research, include correct reading method, record technique, note technique. The data analyze technique was using interactive qualitative analyze. This research result can conclusion that: 1) the types of act to say was used in Vicky Prasetyo discourse say, include: representative act to say (asertive),directive act to say, expresive act to say, and declaration act to say. 2) implicature types was used in Vicky Prasetyo discourse say include implicature having intention refuse, implicature having intention inform, and implicature having invitation intention. 3) Principal deviation of suavity was used in Vicky Prasetyo discourse says include collision of maksim wisdom, maksim philanthropy, and maksim of x'self debasement.